O istnieniu komandorii templariuszy w Sulęcinie i Łagowie = About the existence of templar commandery in Sulęcin and Łagów - Wasilkiewicz, Kamil (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the 13th cenrury the representatives of the powerful Knights Templar reached Polish land. Since they had the protection of dukes and magnates, the Templars built numerous commanderies, at least the two of which were located on the historic Lubusz Land. The activity of the Templars in Leśnica and Chwarszczany is certain, what is proved by the retained sources and monastery buildings existing in these places till the present times.
Keywords: templariusze; Ziemia Lubuska - historia - 13 w.; Sulęcin (woj. lubuskie); Łagów - historia